Ethical issues in molecular epidemiology and studies of gene-environment interactions - Sharp, Richard (Henry Stewart Talks, 2007)
An experiment in science policy: the ethical, legal and social implications (ELSI) program, Environmental response genes, Applying genetic techniques in risk assessment: toxicogenomics, Ethical issues in the application of genomic technologies in public health, Misconceptions about genetic information, Potential misapplications of genomic information or technologies, Discrimination on the basis of genetic information, Problems in assigning responsibility for poor health based upon genetic information, The scope of future research with biological materials: ethical considerations
Reviewed at 2016/02/11